Nordic homicide in deep time: lethal violence in the early modern era and present times - Kivivuori, Janne (Helsinki University Press, 2022)
Nordic Homicide in Deep Time draws a unique and detailed picture of developments in human interpersonal violence and presents new findings on rates, patterns, and long-term changes in lethal violence in the Nordics. Conducted by an interdisciplinary team of criminologists and historians, the book analyses homicide and lethal violence in northern Europe in two eras – the 17th century and early 21st century. Similar and continuous societal structures, cultural patterns, and legal cultures allow for long-term and comparative homicide research in the Nordic context. Reflecting human universals and stable motives, such as revenge, jealousy, honour, and material conflicts, homicide as a form of human behaviour enables long-duration comparison. By describing the rates and patterns of homicide during these two eras, the authors unveil continuity and change in human violence. Where and when did homicide typically take place? Who were the victims and the offenders, what where the circumstances of their conflicts? Was intimate partner homicide more prevalent in the early modern period than in present times? How long a time elapsed from violence to death? Were homicides often committed in the context of other crime? The book offers answers to these questions among others, comparing regions and eras. We gain a unique and empirically grounded view on how state consolidation and changing routines of everyday life transformed the patterns of criminal homicide in Nordic society. The path to pacification was anything but easy, punctuated by shorter crises of social turmoil, and high violence. The book is also a methodological experiment that seeks to assess the feasibility of long-duration standardized homicide analysis and to better understand the logic of homicide variation across space and over time